Penggunaan hidrokolloid untuk melindungi area periwound pada ulkus diabetikum di Klinik Alhuda Wound Care - Alhuda Alhuda; Liza Phonna; Erna Masdiana; Suriani Suriani (Poltekkes Kemenkes Aceh, 2026)
Background: Diabetes mellitus (DM) is a major global health problem. Diabetic ulcers can impair skin and tissue integrity and increase the risk of infection and amputation. Hydrocolloid dressings maintain a moist wound environment and may protect the periwound skin from exudate.Objective: To describe the use of hydrocolloid dressing for periwound protection in two patients with diabetic ulcers.Methods: This descriptive case study involved two purposively selected patients with diabetic ulcers at the Alhuda Wound Care Clinic, Lhokseumawe, from March 17 to 25, 2025. Wounds were assessed using the Winner Scale and hydrocolloid application procedure. The intervention was provided during three sessions over one week as part of the moist wound care.Results: Neither patient developed periwound maceration, and the wound edges improved during the observation period. The Winner Scale scores decreased from 25 to 13 (48%) in patient D and from 26 to 16 (38.5%) in patient A. The manuscript estimated that wound healing would require approximately seven weeks.Conclusion: In these two cases, wound scores decreased, and no periwound maceration was observed during one week of hydrocolloid use. Because this was a descriptive case study with two patients, the findings do not establish effectiveness or causality of the treatment.